Análise teórica da convecção forçada na entrada térmica de fluidos participantes em dutos, considerando os efeitos simultâneos da radiação e da condução axial - Veloso, Dhiego Luiz de Andrade (2019)
Many engineering applications are capable of producing high temperature exhaust gases, making analysis of the flow of participating fluids relevant and necessary in different situations, such as: boilers fire-pipes, propulsion systems, turbocharged engines, among others. The present work aims to analyze the heat transfer in laminar and turbulent flow of participating fluids inside circular and rectangular ducts. It is a problem of simultaneous heat transfer by convection and radiation, hydrodynamically developed and thermally developing. The fluid is treated as gray, purely absorber and emitter of thermal radiation. The duct wall is considered gray and perfectly diffused, being maintained at constant temperature. In the present study, a differential approximation is used to model radiative transference, based on the method of moments, in accordance with some works found in the specialized literature. A hybrid method, numerical-analytical, called Generalized Integral Transformation Technique (GITT), is applied to simultaneously solve the energy equation and the radiative transfer equation. The results, presented in the form of tables and graphs, allow to analyze the influence that the parameters conduction-radiation, optical thickness, contour surface emissivity, Peclet number, Prandtl number and Reynolds number exert in the temperature field and in the Convective, Radiative and Total Nusselt numbers. The significance of the thermal radiation and the behavior of the convective process with and without the inclusion of the radiation is investigated. In the study of laminar flow, three different mathematical models are used to solve the problem, which are compared to each other and demonstrate the versatility of the GITT. In the analysis of the turbulent flow, different turbulence models will be adopted, with different formulations for velocity distribution and for the momentum eddy diffusivity; four situations will be analyzed, based on analytical expressions proposed for the universal velocity profile - "Law of the Wall". The results obtained in the present work were confronted with existing ones in the open literature, in order to validate the presented model.